2022
DOI: 10.3390/ijerph19148708
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alexithymia in Predicting Internet Novel Addiction through Boredom Proneness

Abstract: With the development of the internet, people’s pursuit of reading entertainment has enriched internet novels, but the relevant influencing factors are still unclear. Therefore, we recruited 344 Chinese college students and employed a questionnaire survey to explore the relationship between alexithymia, boredom proneness, and internet novel addiction. The results showed that (1) there was no significant difference between female and male college students in terms of alexithymia and boredom proneness, whereas ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Then, the use of self-report questionnaires introduces the potential for biases related to social desirability, participants’ difficulty in accurately assessing themselves, and misinterpretation of questions; therefore, this topic should be explored further by including, for example, qualitative and/or other-report measures. Moreover, we did not use any measure of alexithymia, despite its possible involvement in the development of boredom [ 30 , 51 ]; hence, future studies should include different measures of emotion dysregulation to provide a more nuanced perspective on this matter. Finally, the cross-sectional research design did not enable us to unravel the causal and temporal relations among the constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the use of self-report questionnaires introduces the potential for biases related to social desirability, participants’ difficulty in accurately assessing themselves, and misinterpretation of questions; therefore, this topic should be explored further by including, for example, qualitative and/or other-report measures. Moreover, we did not use any measure of alexithymia, despite its possible involvement in the development of boredom [ 30 , 51 ]; hence, future studies should include different measures of emotion dysregulation to provide a more nuanced perspective on this matter. Finally, the cross-sectional research design did not enable us to unravel the causal and temporal relations among the constructs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, elevated levels of alexithymia were found to be related to high levels of trait boredom in a sample of undergraduate students [ 30 ]. Moreover, Liu et al [ 51 ] found a significant and positive association between boredom propensity and alexithymia in a group of Chinese college students, with boredom propensity partially mediating the effect of alexithymia on Internet novel addiction. To our knowledge, only two works, both conducted on adult samples during the COVID-19 pandemic, have considered emotion dysregulation as conceptualized by Gratz and Roemer [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 First of all, individuals with alexithymia increase their susceptibility to boredom due to deficiencies in their attention-evaluation cognitive system. 11,23,58 People with alexithymia have a higher tendency to be bored than the general population. 24 The higher the degree of alexithymia, the more pronounced the tendency to boredom.…”
Section: The Mediating Effect Of Meaning In Lifementioning
confidence: 99%
“…24 The higher the degree of alexithymia, the more pronounced the tendency to boredom. 58 It's a sign of a lack of meaning. In addition, individuals with high alexithymia often suffer from varying degrees of quality of life impairment, 25,26 and they often have difficulty finding meaning in their lives.…”
Section: The Mediating Effect Of Meaning In Lifementioning
confidence: 99%